1993
DOI: 10.1111/j.1471-4159.1993.tb03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally Regulated Secreted Factors Control Expression of Muscarinic Receptor Subtypes in Embryonic Chick Retina

Abstract: Two molecular mass subtypes of muscarinic receptor are expressed by the chick retina (72 and 86 kDa). During development, the ratio of subtypes changes, with the 72-kDa form becoming predominant. We have found that subtypes switch can occur in retina cell culture, and have investigated factors that influence this in vitro increase in the 72-kDa receptor. Increases similar to those in vivo occurred when cells were cultured at 10(5) cells/cm2, but not at 10-fold lower density. High-density cultures, maintained o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The results of this study indicate that nAChRs begin to be expressed in the chick retina very early, around E4.5, which is well before the first appearance of choline acetyltransferase in neurons at E6.5 (Spira et al, 1987). Muscarinic acetylcholine receptors are also present in the nervous system prior to synapse formation (Dryer and Chiappinelli, 1985;Skorupa and Klein, 1993). It is interesting to note that another component of the cholinergic system, acetylcholinesterase, also first appears in the chick retina by E4.5 (Shen et al, 1956).…”
Section: Discussionmentioning
confidence: 64%
“…The results of this study indicate that nAChRs begin to be expressed in the chick retina very early, around E4.5, which is well before the first appearance of choline acetyltransferase in neurons at E6.5 (Spira et al, 1987). Muscarinic acetylcholine receptors are also present in the nervous system prior to synapse formation (Dryer and Chiappinelli, 1985;Skorupa and Klein, 1993). It is interesting to note that another component of the cholinergic system, acetylcholinesterase, also first appears in the chick retina by E4.5 (Shen et al, 1956).…”
Section: Discussionmentioning
confidence: 64%
“…A variety of studies have determined the appearance of neurotransmitters, their biosynthetic enzymes, and their respective receptors in the developing chick retina. For example, the nicotinic and the muscarinic acetylcholine receptor, as well as glutamate receptors are already expressed very early in development (Vogel and Nirenberg, 1976;Sugiyama et al, 1977;Somohano et al, 1988;Matter et al, 1990;Skorupa and Klein, 1993;Hamassaki-Britto et al, 1994). Similarly, low levels of benzodiazepin-binding GABAA receptor subunits have been detected already at E7 (Altstein et al, 1981;Shah and Hausman, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, chicken retina CM promotes the differentiation of cholinergic neurons of the retina (de Mello et al, 1990). Skorupa and Klein (1993) showed that a factor produced by mature retinal cells was involved in mAChR gene transcription. Subsequent research showed that mature but not immature retinal cells, probably Muller glia, secrete a developmentally regulated protease-sensitive factor that induces a selective increase in the muscarinic cm2 mRNA and protein (McKinnnon et al, 1998;Belmonte et al, 2000).…”
Section: Introductionmentioning
confidence: 99%